Asia's naval expansion an arms race in the making? - Till, Geoffrey (Adelphi (Series) (International Institute for Strategic Studies), 2012)
The navies of China, India and to a lesser extent Japan are expanding rapidly at present. This has the potential to alter the US-dominated naval balance in Asia-Pacific but it also raises a question: are the region's powers involved in a naval arms race? Naval development is and always has been a crucial indicator of economic and political development. It shows the emergence of a significant shift in strategic weight from West to East. But within the Asia-Pacific Region, alongside growing economic and institutional integration, there are geo-political tensions that threaten the regions stability and peace. The balance between the two determines the form that naval development in that region is taking. Some aspects of this suggest the beginnings of a naval arms race that would have profound consequences for the region and the world.